Neuroprotective and Nootropic Activity of Carica Papaya Seeds on Diabetes induced Cognitive Decline in Rats: Activity of Carica Papaya Seeds on Diabetes induced Cognitive Decline - Venkateshwarlu, Eggadi; Srilatha, Keshaveni; Sheshagiri Sharvana Bhava, Bandaru; Umasankar, Kulandaivelu (Iranian Journal of Pharmaceutical Sciences, 2018)
The aim of present study is to investigate neuroprotective and nootropic activity of Petroleum Ether Extract of Carica papaya seeds (PEECPS) on diabetic induced cognitive decline rats. Rectangular maze and morris water maze models were used to evaluate nootropic activity and neuroprotective effects were studied by estimating acetyl cholinesterase (AchE), malondialdehyde (MDA), superoxide dismutase (SOD), nitric oxide (NO), catalase (CAT) and glutathione (GSH) levels in the brains of diabetic rats. In rectangular maze and morris water maze models, 400 mg/kg of PECPS were shown the significant effect compared with diabetic control on day 75. Significant decrease in AchE (P<0.001), MDA (P<0.01), NO (P<0.05) and significantly (P<0.01) increased levels of SOD, CAT and GSH with PECPS (200 and 400 mg/kg) compared with diabetic control. There is a need of further studies on Carica papaya seeds as it showed protection against diabetes induced cognitive decline to reveal its mode of action.